SOSIALISASI MENCUCI TANGAN DENGAN BENAR DAN PELATIHAN PEMBUATAN PAPER SOAP DI SMP NEGERI 1 SORKAM, KECAMATAN SORKAM KABUPATEN TAPANULI TENGAH - Emy Hariati; Hendra; Nuri Ramadhan; Leni Malinda; Sisilia Florina Yanti; Nurbaity Situmorang; Dewi Novina Sukapiring; Mastari Ramadhani; Juhardi Sembiring; Rizky Ananda; Fatimah Pohan; Suharsih; Syarifah Ainun Harahap; Rara Astili Siregar (Jurnal Pengabdian Masyarakat, 2024)
Regular handwashing is the first 5M health protocol and is effective in preventing the transmission of viruses and diseases. However, mobility and activities cause many to neglect to always have soap on hand when travelling. For this reason, a simple innovation for the use of soap is needed, namely by using paper soap. Paper soap is much more practical in its use and easy to carry anywhere. Based on the survey of the service team, several problems were found, such as students who were often absent from school due to illness, students' low understanding of hand washing with soap, and students' lack of knowledge in making paper soap. The purpose of this community service is to improve students' knowledge and skills in applying the six steps of handwashing with soap and to improve students' skills in making paper soap with natural ingredients. This community service was carried out by providing counselling on the importance of hand washing, assistance in making paper soap from natural ingredients to students. The results obtained from this service are an increase in knowledge and creativity of students who initially did not know how to make paper soap to know, and increased student understanding of the steps of good and correct hand washing.